MORAL VALUE FOUND IN THE MOVIE “DEAD POETS SOCIETY” BY PETER WEIR - Ginting, Jusuf Gatra; Kristiana, Vera (Fakultas Sastra UMN AL Washliyah, 2025)
The aim for this research first to identify the types of moral values in the movie Dead Poets Society by Peter Weir. Second, to find out how these values shape the characters' journeys and contribute to the film’s overall message of individuality, integrity, and the importance of pursuing one's passions despite societal pressures. This research used qualitative research method with descriptive types. The result of this research show that there are 9 types of moral values in Dead Poets Society such as the moral value of bravery, honesty, steadfastness, sympathy for others, cooperativeness, thankfulness, kind-heartedness, trustworthiness, and love and affection.